Hip joints mobility in patients with lumbosacral disc disorders - Krajewski, Stanisław; Krajewska, Małgorzata; Kucharczuk-Kopycińska, Magda; Litwinowicz, Aleksander (Journal of Education, Health and Sport, 2016)
Purpose. The authors were influenced to carry out the research by observing the patients suffering from discopathy with frequent faulty positioning of lower limbs – genu valgum, which was accompanied by increased range of external hip joint rotation. The assumed thesis was that wrong mobility of hip joints is conducive to development of lumbosacral disc disorder. Methods.73 people were subjected to the research among whom 36 had discopathy and were qualified for surgical treatment in Neurosurgery Clinic of 10thMilitary Hospital in Bydgoszcz. The rest (control group- 37 people) did not have any lumbosacral disc disorders. Hip joints mobility was measured according to SFTR method. The range of mobility was mesured in all planes. Results. The relation between occurrence of discopathy in LS spine and increased values of mobility in hip joints was noted. The most substantial mobility differences between the research and control groups were related internal / external rotation. Conclusions. The developmnet of disorders in these segments of spine is influnced by biomechanical factors in pelvis and lower limbs. Confirmation of the results in a bigger-scale research may result in introduction of prophylaxis of disc disorders in people with hypermobility of hip joints even at their teen age.